Coffee wilt disease - Flood, Julie (Burleigh Dodds Series in Agricultural Science, 2021)
In the early 20th century, coffee wilt disease (CWD) caused by the vascular wilt pathogen, Fusarium xylarioides, spread across Africa destroying coffee trees, reducing yields and significantly impacting producer livelihoods. Through systematic sanitation and establishment of breeding programmes in affected countries, CWD appeared to decline. However, the disease re-emerged and increased to epidemic proportions in the 1990s affecting robusta coffee in DRC, Uganda and Tanzania and arabica coffee in Ethiopia. In 1999, 14.5 million robusta coffee trees were estimated to have been destroyed in Uganda alone. This chapter discusses the history, impact, symptoms, cause and spread of CWD. A summary of the Regional Coffee Wilt Programme (RCWP) which examined many aspects of the disease and its management is also provided. Future research trends include host specificity, underlying resistance mechanisms and the role of alternative hosts. Investigation of pathogen ecology is needed to allow greater focus on agroecological management practices.